Pengetahuan Keluarga Tentang Metode FAST dengan Perilaku Keluarga dalam Penanganan Awal Stroke di Poli Saraf - Vicky Indriyani, Renata; I Ekatrina Wijayanti, M; Lidya, Herlin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Stroke is a medical condition that requires immediate treatment because it can cause permanent brain damage or even death if not treated quickly. Delays in medical treatment can lead to increased rates of morbidity and even death. Therefore, family knowledge about early detection of stroke is needed. Families who know about early stroke detection will be able to take patients to hospital more quickly for immediate treatment, thereby reducing the risk of permanent disability. The aim of this study was to analyze the relationship between family knowledge about the FAST method and family behavior in the initial treatment of stroke at the Antonio Baturaja Hospital polyclinic. The method used in this research was cross sectional, with a total of 33 respondents taken using a purposive sampling method from families whose family members received treatment at the Neurology Clinic at Antonio Baturaja Hospital. The research results showed that 63.6% (21 respondents) had a high school education, with a knowledge score of 97% (32 respondents) had sufficient knowledge and a score for family behavior of 100% (33 respondents) was declared good. This study used the Spearman correlation test where the p value was 0.039 and r 0.326, so there was a significant relationship between family knowledge and family behavior in early stroke management. The conclusionof this study is that there is a significant relationship between family knowledge regarding the FAST method and family behavior in early stroke management with a positive correlation, meaning the higher the knowledge, the better. Suggestions to hospitals and nurses to provide education regarding early detection using the FAST method to families and patients, so that families and patients understand more about early detection of stroke using the FAST method.